(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Learning vocabulary is one of the most important aspects of acquiring a second language, especially in situations where two languages are spoken, such as English-Uzbek university classes. The common practice of memorizing through rote learning does not always bring long-term retention and active use of the new vocabulary over and above that, thus coming up with teaching techniques that are new, fun and lively is the solution. The present research investigates both theoretically and practically the effectiveness of three innovative vocabulary learning techniques: Word Theater, Mnemonic Battles, and Translation Jigsaw. The study is based on well-known second language acquisition research, including that of Nation, Schmitt, Webb, and Laufer, and it discusses how these methods foster.